2017
DOI: 10.1590/1678-457x.29116
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted aqueous enzymatic extraction of oil from perilla seeds and determination of its physicochemical properties, fatty acid composition and antioxidant activity

Abstract: Response surface methodology (RSM) was used to optimize ultrasound-assisted aqueous enzymatic extraction (UAAEE) conditions for perilla seed oil. Under the optimum conditions-which were a liquid-to-solid ratio of 4.4:1, a hydrolysis time of 2.66 h, a hydrolysis temperature of 50.87 °C and an ultrasound treatment time of 24.74 min-an oil yield of 31.34% was obtained. Comparisons of the physicochemical characteristics of oil obtained using UAAEE with those of oil obtained by solvent extraction (SE oil) and cold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…Among the monounsaturated fatty acids (MUFAs), eicosenoic acid and erucic acid were dominant, with contents varying from 0.17% to 0.22% and 0 to 0.17%, respectively. In addition, oleic acid increased from 0.02% to 0.20%, which is lower than the 16.92% that was reported by Li et al (). The oleic acid content of perilla seed oil in this study is lower than that previously reported, while the level of linolenic acid is higher.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Among the monounsaturated fatty acids (MUFAs), eicosenoic acid and erucic acid were dominant, with contents varying from 0.17% to 0.22% and 0 to 0.17%, respectively. In addition, oleic acid increased from 0.02% to 0.20%, which is lower than the 16.92% that was reported by Li et al (). The oleic acid content of perilla seed oil in this study is lower than that previously reported, while the level of linolenic acid is higher.…”
Section: Resultscontrasting
confidence: 68%
“…This can provide a reference point for further study. Li et al () reported that perilla seed oil is a great source of phenolic compounds that can play an important role in antioxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, perilla seeds contain different polyphenols or flavones (rosemarinic acid, luteolin, quercetin, catechin, and so on) (Asif, 2011). As a consequence, perilla seed oil (PSO) is typically obtained through different methodologies, either by extraction using organic solvents or by ultrasound‐assisted aqueous enzymatic extraction or by extraction using compressed fluids (Li et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that the ALA in this study was higher than all previous reports. Ultrasonic-assisted aqueous enzymatic extraction using response surface provided 31.34% oil yield containing ALA as major component of 64.05% (Li et al, 2017). Similarly, soxhlet extraction using hexane as solvent and cold pressing extraction exhibiting 35.20% and 28.60%, respectively of perilla oil yields gave lower content of ALA at 62.26% and 60.11%, respectively (Li et al, 2017).…”
Section: Gc-ms Analysis Of Fatty Acid Compositions In Perilla Oilmentioning
confidence: 97%
“…Ultrasonic-assisted aqueous enzymatic extraction using response surface provided 31.34% oil yield containing ALA as major component of 64.05% (Li et al, 2017). Similarly, soxhlet extraction using hexane as solvent and cold pressing extraction exhibiting 35.20% and 28.60%, respectively of perilla oil yields gave lower content of ALA at 62.26% and 60.11%, respectively (Li et al, 2017). Supercritical fluid extraction of perilla oil using carbondioxide and LPG could extract the linolenic acid as a majority fatty acid of 58.00% and 57.24%, respectively (Scapin et al, 2017).…”
Section: Gc-ms Analysis Of Fatty Acid Compositions In Perilla Oilmentioning
confidence: 99%